Performance in male and female elite tennis across season of birth - Blanch, A.; Solé, S. (Chronobiology International, 2021)
In the field of sports, there is an overrepresentation of athletes born in the initial months of the selection year, and an underrepresentation of athletes born in the latter months of the selection year. This season of birth effect appears to lead to a disadvantage in performance, even though with a considerable variability regarding age, sex, and skill. This study addressed season of birth effects on performance with the best one hundred male and female tennis players in the world. Specifically, we examined whether season of birth moderates the association of body height and ranking position with tennis performance. The main findings indicated that body height and rank associated in the expected direction with first service wins, break points saved, and a success rate describing the ratio of match wins to match defeats. For females born later in the selection year, however, height was unrelated to the percentage of first service wins or break points saved, and occupying higher positions in the ranking did not contribute to improve the ratio of wins to defeats. These findings suggest that season of birth effects on performance might operate for women but not for men when comparing highly selected populations such as the best tennis players in the world.